Pediatric Trauma And Emergency Surgery: An International Cross-sectional Survey Among Wses Members. - Martin Reichert; Massimo Sartelli; Ingolf H. Askevold; Jaqueline Braun; Markus A. Weigand; Matthias Hecker; Vanni Agnoletti; Federico Coccolini; Fausto Catena; Winfried Padberg; Jens G. Riedel; Andreas Hecker; et al. (BMC, 2024)
The WSES pediatric emergency surgery collaboration group Agron Dogjani, Akira Kuriyama, Alberto Porcu, Aleix Martínez-Pérez, Alessandro Coppola, Alessandro Spolini, Alessio Giordano, Alexandros Kyriakidis, Ali Yasen Y. Mohamedahmed, Anastasia Vasilopoulou, Andee Dzulkarnaen Zakaria, Andrea Balla, Andreas Fette, Andrey Litvin, Anna Guariniello, Arda Isik, Aristotelis Kechagias, Ashrarur Rahman Mitul, Belinda De Simone, Biagio Zampogna, Bruno Sensi, Carlo Gazia, Charalampos Seretis, Cristine Brooke, Davide Luppi, Diego Coletta, Diego Sasia, Diletta Corallino, Dimitrios Chatzipetris, Dimitrios Schizas, Eftychios Lostoridis, Elmuiz A. Hsabo, Emmanouil Kaouras, Emmanuel Schneck, Enrico Pinotti, Evgeni Dimitrov, Fabrizio D’Acapito, Federica Saraceno, Fikri Abu-Zidan, Francesca Maria Silvestri, Francesco Favi, Francesco Fleres, Francesk Mulita, Gabriela Nita, Gennaro Martines, Gennaro Mazzarella, Gennaro Perrone, Giorgio Giraudo, Giulia Bacchiocchi, Giulio Argenio, Giuseppe Brisinda, Giuseppe Currò, Giuseppe Palomba, Gustavo P. Fraga, Hytham K. S. Hamid, Ioannis Katsaros, Ionut Negoi, Joel Noutakdie Tochie, Justin Davies, Kenneth Y. Y. Kok, Konstantinos G. Apostolou, Konstantinos Lasithiotakis, Konstantinos Tsekouras, Larysa Sydorchuk, Leandro Siragusa, Leonardo Solaini, Luca Ferrario, Luis Buonomo, Maciej Walędziak, Mahir Gachabayov, Maloni Bulanauca, Manish Kumar Agrawal, Marco Ceresoli, Maria Chiara Ranucci, Maria Petridou, Mario D’Oria, Massimiliano Veroux, Maximos Frountzas, Michel Paul Johan Teuben, Miklosh Bala, Mirja Amadea Minger, Miroslava Gonçalves, Natasha Sharma, Nicolò Tamini, Noushif Medappil, Orestis Ioannidis, Pietro Bisagni, Razrim Rahim, Ricardo Alessandro Teixeira Gonsaga, Roberta Ragozzino, Roberto Bini, Roberto Cammarata, Ruslan Sydorchuk, Salomone Di Saverio, Selmy S. Awad, Semra Demirli Atici, Serhat Meric, Sharfuddin Chowdhury, Sofia Xenaki, Tadeja Pintar, Teresa Perra, Timothy C. Hardcastle, Valerio Voglino, Varut Lohsiriwat, Victor Kong, Voskidis Christos & Wietse Zuidema